Crescimento de mudas clonais de Hevea brasiliensis Muell. Arg em diferentes regimes térmicos, concentração de CO2 e níveis de água no solo - Costa, Erilva Machado (2015)
The intensification of human activities has resulted in significant increase in the concentration of greenhouse gases, including changing the thermal regimes and hence the water balance and can influence the growth of plants. The objective of this study was to evaluate the initial growth and determine physiological patterns of rubber tree clones under adverse weather conditions. For this two experiments were established in order to assess the influence of CO2 concentrations and different water regimes in contrasting microclimates. The studies were carried out in air-conditioned greenhouses, with controlled temperature and relative humidity, belonging to the Meteorological Laboratory Ecophysiology and Forestry of the Federal University of Espirito Santo in the city of Jerônimo Monteiro, ES. In the study presented in Chapter I, two clones of H. brasiliensis (RRIM 600 and FX 3864) were evaluated under microclimate conditions and atmospheric concentrations of CO2 contrasting. Thus, two experiments were set up, one for each clone, following a completely randomized design in a 2x2 factorial design (two microclimate conditions x two concentrations of CO2) with six repetitions, each repetition consisting of a plant. For controlling CO2 concentrations, we used open-top chambers (OTC - Open Top Chambers) with automatic control of CO2 injection, allocated within two greenhouses acclimatized between the months of September to December. In the study presented in chapter II, two clones of H. brasiliensis (RRIM 600 and FX 3864) were evaluated under microclimate conditions and different water regimes between the months of September to November. Thus, two experiments were set up, one for each clone, following a completely randomized design in a 2x2 factorial design (two water regimes x two microclimate conditions), with five replications, each replication consisted of a plant. The available water in the substrate was determined by using data obtained water retention curve in the soil and, from these data it was established volume of water for each water system. The water control was performed by daily weighing vessel, using a precision balance. At the end of each experiment was performed plant growth analysis by obtaining the total dry matter and its partitions, as well as leaf area, leaf specific area. To evaluate the physiological responses of plants, there was gas exchange measurements and quantification of photosynthetic pigments content for both experiments. Furthermore, for the experiment Chapter I, of the gas exchange measurements for curve fitting were performed A/FFFA and A/Ci to obtain photosynthetic parameters. The data from the two experiments were subjected to analysis of variance, and when significant, the averages were compared by Tukey test at 5% probability. Clones showed higher growth, higher net assimilation rates of CO2 and intrinsic efficiency of water use by increasing the concentration of CO2, regardless of microclimates. Using the variables growth and physiological responses is evident in this study that the rubber tree clones, RRIM 600 and FX 3864, have a greater sensitivity to microclimate conditions with low air demand, independent of [CO2]. Since, through the analysis of the curves A/FFFA and A/Ci, clones have higher photosynthetic performance in response to light when kept under high atmospheric demand. The reduction of 50% of available water in the soil for the clones RRIM 600 and FX 3864, was sufficient to reduce growth, demonstrating high susceptibility of clones to drought. However, the clone FX 3864 was more tolerant to reduced water availability compared to the RRIM 600 clone.